Kidney Failure is Associated with Worse Pancreas Graft Survival in Simultaneous Pancreas and Kidney Transplantation. (July 2018) - Girman, Peter; Lipar, Kvetoslav; Marada, Tomas; Kocik, Matej; Koznarova, Radomira; Fronek, Jiri; Saudek, Frantisek
Abstract : Introduction: Kidney graft loss in simultaneous pancreas and kidney (SPK) recipients can be associated with worsened pancreas survival as the both organs come from the same donor and may bare a similar risk of rejection. The aim of this retrospective analysis was to evaluate pancreas survival in SPK transplant recipients with failed kidney grafts. Method: The institutional registry data since 1986 to 2016 from 522 SPK type 1 diabetic recipients was retrospectively evaluated. The recipients were divided into 2 groups. Group A (n=426) comprised patients with functioning first kidney graft, group B (n=96) included recipients with failed kidney grafts at time of the analysis. Pancreas failure was defined as return to intensified insulin regimen, graftectomy or death. Survival curves were plotted according to Kaplan-Meyer method and differences between curves were tested with long-rank test. Survival was calculated from the date of the first SPK transplantation. Kidney failure was defined as graftectomy, return to dialysis or kidney retransplantation. Results: Ten year overall recipient and pancreas survival rates in 522 SPK translants were 79 and 60%, respectively. Patient survival in group B was significantly worse than in group A (74% vs 82%, p=0.049). Similarly, non-censored pancreas graft survival rate was significantly worse in recipients with failed kidney than in those with preserved function of the first kidney graft (51% vs 66%, p=0.007). Altogether 36 (39%) pancreatic grafts failed in group B and only 73 (16%) in group A. The most frequent cause of the pancreatic graft failure was rejection in Group B (20/36, 55%), while in Group A, most pancreatic grafts failed due to early non-immune reasons (57/73, 78%). A subgroup of recipients with failed kidney grafts followed by subsequent kidney retransplantation was analyzed separately (n=55). Their 10-year patient and pancreas graft survival rates were 97 and 74%, respectively, which is was worse than in those in whom the first kidney graft did not fail, but was better than in those who stayed on dialysis. Conclusion: The results from our retrospective analysis showed that pancreas survival is significantly shorter in recipients with failed fist kidney graft. Rejection seems to be responsible for most of pancreatic graft losses. In contrast to some previous reports, kidney retransplantation did not negatively impact pancreas survival in our center. Supported by Ministry of Health, Czech Republic – conceptual development of research organization (Institute for Clinical and Experimental Medicine – IKEM, IN00023001).